(untitled) (Environmental Science Journal (esjo) : Jurnal Ilmu Lingkungan, 2025)
This study aims to analyze the effect of liquid organic fertilizer (POC) from tofu waste on the growth of tomatoes (Solanum lycopersicum Mill.). The study was conducted in September - December 2024 at the Green House of the Faculty of Science and Technology, Universitas PGRI Palembang. Data were analyzed at the Biology Laboratory of the Business Science Center, Universitas PGRI Palembang. Data were obtained quantitatively using analysis of variance (ANOVA). The experimental design used was a Completely Randomized Design (CRD) with 6 treatments and 4 repetitions. The treatments in this study were the administration of liquid tofu waste fertilizer with concentrations of 0%, 5%, 10%, 15%, 20%, and 25%. The research data obtained were analyzed using Analysis of Variance (ANOVA) at the 5% level, and significantly different treatments were further tested with BNJ at the 5% level. carried out with Honestly Significant Differences (BNJ) at the 5% level. The results showed that liquid organic fertilizer (POC) from tofu liquid waste had no significant effect on the growth of plant height, number of leaves, stem diameter, and wet weight of tomato plants (Solanum lycopersicum Mill). The application of liquid organic fertilizer (POC) from tofu liquid waste with P4 treatment was the best result in all parameters, producing an average plant height of 7.15 cm, number of leaves 5 strands, stem diameter 0.05, and wet weight of tomato plants 0.22 grams.